Topical corticosteroid withdrawal ('steroid addiction'): an update of a systematic review. (3rd April 2022) - Hwang, Jonwei; Lio, Peter A.
Abstract: Background: Topical corticosteroid withdrawal is an entity associated with chronic steroid use and misuse that has not been fully described. Objective: To further characterize this entity, elucidate relevant clinical features, and investigate possible treatments we provided an update to a systematic review done in 2015. Methods: We searched Ovid Medline, Pubmed, and Cochrane library for terms related to topical corticosteroid withdrawal from April 2014 to September 2020. Results: This entity usually occurs after prolonged use of moderate- to high-intensity topical steroid usage usually on the face. It is most common in women and many patients present due to improper use such as for cosmetic reasons. Symptoms include erythema, itchiness, and burning; secondary lesions are common scales. Limitations: Due to the paucity of available study, we elected to include all articles found which led to limitations being lack of heterogeneity, diversity of outcome measures reported, and a higher risk of bias in some included studies. Conclusion: Topical corticosteroid withdrawal should be suspected in patients presenting with prolonged usage, erythema, and burning or itch. Patient education and follow up is important to address improper usage. Future studies should focus on comparison group studies to investigate treatment and risk factors.